Boltzmann Sampling by Degenerate Optical Parametric Oscillator Network for Structure-Based Virtual Screening - Sakaguchi, Hiromasa; Ogata, Koji; Isomura, Tetsu; Utsunomiya, Shoko; Yamamoto, Yoshihisa; Aihara, Kazuyuki (Entropy (Basel, Switzerland), 2016)
A structure-based lead optimization procedure is an essential step to finding appropriate ligand molecules binding to a target protein structure in order to identify drug candidates. This procedure takes a known structure of a protein-ligand complex as input, and structurally similar compounds with the query ligand are designed in consideration with all possible combinations of atomic species. This task is, however, computationally hard since such combinatorial optimization problems belong to the non-deterministic nonpolynomial-time hard (NP-hard) class. In this paper, we propose the structure-based lead generation and optimization procedures by a degenerate optical parametric oscillator (DOPO) network. Results of numerical simulation demonstrate that the DOPO network efficiently identifies a set of appropriate ligand molecules according to the Boltzmann sampling law.